The Fraud Actors in Indonesia According to Fraud Indonesia Survey - Posma Sariguna Johnson Kennedy; Santi Lina Siregar (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
The Association of Certified Fraud Examiners issues an survey of fraud behavior, is the Survey Fraud Indonesia. This paper wants to see the survey in terms of who the actor of fraud is. The analysis is by looking at the descriptive statistics of the secondary data generated by the survey. The results show that the fraud losses at any level are largely done by men. The average age of most fraud perpetrators is aged 36-45 years, then performed by the age of 46-55 years. The age shows that fraud actors are in a very productive position and are usually in the top position. Education of the largest perpetrators of fraud in Indonesia is a scholar and above.Keywords: Fraud, Corruption, Indonesian Fraud Survey